THE SYNTHESIS AND NMR STUDY ON THE STABILITY OF DIMETHYLMETHOXOPLATINUM(IV) COMPLEXES - Sutopo Hadi (Universitas Gadjah Mada, 2005)
he synthesis of two stable platinum(IV) complexes containing methoxo ligand, [Pt(CH3)2(OCH3)(OH)py2] (1) and fac-[Pt(CH3)2(OCH3)(H2O)3] (2), has been successfully performed. Complex 1 was prepared by oxidative addition reaction of cis-[Pt(CH3)2py2] with dry methanol, and a subsequent reaction of 1 with 70 % HClO4 in water produced the platinum complex 2. The stability of complex 2 in acidic aqueous solution was investigated and monitored with 1H and 195Pt NMR. The platinum complex 2 was found to be quite stable toward hydrolysis and no -hydride elimination was observed.